Handling uncertain data in subspace detection - Fernandes, Leandro A.F.; Oliveira, Manuel M. (Pattern recognition, 2014)
Experimental data is subject to uncertainty as every measurement apparatus is inaccurate at some level. However, the design of most computer vision and pattern recognition techniques (e.g., Hough transform) overlooks this fact and treats intensities, locations and directions as precise values. In order to take imprecisions into account, entries are often resampled to create input datasets where the uncertainty of each original entry is characterized by as many exact elements as necessary. Clear disadvantages of the sampling-based approach are the natural processing penalty imposed by a larger dataset and the difficulty of estimating the minimum number of required samples. We present an improved voting scheme for the General Framework for Subspace Detection (hence to its particular case: the Hough transform) that allows processing both exact and uncertain data. Our approach is based on an analytical derivation of the propagation of Gaussian uncertainty from the input data into the distribution of votes in an auxiliary parameter space. In this parameter space, the uncertainty is also described by Gaussian distributions. In turn, the votes are mapped to the actual parameter space as non-Gaussian distributions. Our results show that resulting accumulators have smoother distributions of votes and are in accordance with the ones obtained using the conventional sampling process, thus safely replacing them with significant performance gains. •A general solution for detecting data alignments (subspaces) in unordered multidimensional data.•Our approach can handle both exact data as well as data containing Gaussian distributed uncertainties.•Our approach allows the concurrent detection of different types of data alignments.•Our approach allows the detection of data alignments in heterogeneous datasets.